Patung burung kenyalang dalam budaya masyarakat iban - Steve, anak Alexander Pateh (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This research is about kenyalang traditional wood carving in Iban's culture. Besides, this finding is also to identify the rules changing in kenyalang traditional carving in Iban culture nowadays. In the same times, this finding will make a comparison between three main location that vey famous with kenyalang traditional wood carving; Balleh Kapit, Lubok Antu Sri Aman and Layar Betong.